Helping new teachers stay and thrive in rural schools. (December 2021) - Brenner, Devon; Azano, Amy Price; Downey, Jayne
Among the many challenges facing rural administrators, recruiting and retaining teachers is often at the top of the list. Given the time and energy they must invest to successfully attract, recruit, and hire a new teacher, there is a significant need to adopt strategies that will help to retain those new teachers. Rural administrators can support new teachers so that they stay — and thrive — in rural districts by connecting teachers with the community, supporting place-based practices in the classroom, and helping new teachers build relationships both in and out of school .